Simultaneous Determination of TetracyclinesResidues in Bovine Milk Samples by Solid Phase Extraction and HPLC-FL Method - Mehra Mesgari Abbasi; Hossein Babaei; Masoud Ansarin; Ashraf-; Mahboob Nemati (Tabriz University of Medical Sciences, 2011)
Introduction:Tetracyclines (TCs) are widely used in animal husbandry and their residues in milk may resultinharmful effects on human. The aim of this study was to investigate the presence of TCs residues in various bovine milk samples from local markets of Ardabil, Iran. Methods:One hundred and fourteen pasteurized, sterilized and raw milk samples were collected from markets of Ardabil. Tetracycline, Oxytetracycline and Chlortetracycline (TCs) residues extraction carried out by Solid Phase Extraction method. Determination of TCs residues were performed by high performance liquid chromatography (HPLC) method using Fluorescence detector.Results: The mean of total TCs residues in all samples (114 samples) was 97.6 ±16.9ng/g and that of pasteurized, sterilized and raw milk samples were 87.1 ± 17.7, 112.0 ± 57.3 and 154.0 ± 66.3ng/g respectively. Twenty five point four percent of the all samples, and24.4%, 30% and 28.6% of the pasteurized, sterilized and raw milk samples, respectively had higher TCs residues than the recommended maximum levels (100ng/g). Conclusion:This study indicates the presence of tetracycline residues more than allowed amount. Regulatory authorities should ensure proper withdrawal period before milking the animals and definite supervisions are necessary on application of these drugs.